Producción de Hortalizas en Ambientes Protegidos: Estructuras para la Agricultura Protegida - Bielinski M. Santos; Henner A. Obregón-Olivas; Teresa P. Salamé-Donoso (EDIS)
HS1182, a 5-page illustrated, Spanish-language fact sheet by Bielinski M. Santos, Henner A. Obregón-Olivas, and Teresa P. Salamé-Donoso, describes the advantages and disadvantages of various types of structures used in protected vegetable production. Published by the UF Department of Horticultural Sciences, August 2010.